Hydrogels with Cell Adhesion Peptide‐Decorated Channel Walls for Cell Guidance. Issue 15 (8th July 2020) - Wang, Shuang; Sarwat, Mariah; Wang, Peng; Surrao, Denver C.; Harkin, Damien G.; St John, James A.; Bolle, Eleonore C. L.; Forget, Aurelien; Dalton, Paul D.; Dargaville, Tim R.
Abstract: A method is reported for making hollow channels within hydrogels decorated with cell‐adhesion peptides exclusively at the channel surface. Sacrificial fibers of different diameters are used to introduce channels within poly(ethylene glycol) hydrogels crosslinked with maleimide‐thiol chemistry, which are backfilled with a cysteine‐containing peptide solution which is conjugated to the lumen with good spatial efficiency. This allows for peptide patterning in only the areas of the hydrogel where they are needed when used as cell‐guides, reducing the amount of required peptide 20‐fold when compared to bulk functionalization. The power of this approach is highlighted by successfully using these patterned hydrogels without active perfusion to guide fibroblasts and olfactory ensheathing cells—the latter having unique potential in neural repair therapies. Abstract : The physical and chemical processes for creating synthetic hydrogels with cell‐adhesion peptides patterned exclusively within tubular pores is presented. The method relies on removal of sacrificial fibers followed by addition of a cysteine‐containing peptide to react with maleimide groups on the hydrogel. Demonstration of the ability to guide cells with nerve regeneration potential is presented.